Interpretation of Javanese Ethics in Handling Deviant Behavior of Adolescents: An Interpretative Phenomenological Analysis - Suprihatiningsih Suprihatiningsih; Tri Marhaeni Pudji Astuti; Agustinus Sugeng Priyanto; Sunarto Sunarto (Universitas Pendidikan Ganesha, 2024)
This study aims to understand the application of Javanese ethical values in dealing with deviant behavior of adolescents in Bandengan Fishing Village, Kendal Regency. Using Interpretive Phenomenological Analysis (IPA), this study involved five adolescents with a history of deviant behavior and community leaders active in Javanese ethics-based intervention programs. Data was collected through in-depth interviews (January–April 2024) and Focus Group Discussions (FGDs) (May–June 2024) that explored perceptions, experiences, and strategies for overcoming social stigma. The study participants, consisting of adolescents with a history of deviant behavior and community leaders who are considered to have insight into Javanese ethics, offered diverse perspectives on concepts such as gotong royong (cooperation), tepo seliro (mutual respect), and rukun (harmony) in the context of behavior formation. The analysis results found main themes, including the importance of social acceptance in building adolescents' sense of self-esteem, the role of community support in building positive behavior, and the influence of instilling local values in strengthening adolescent mental resilience. These findings suggest that Javanese ethical values not only serve as a method of handling behavior but also as a tool to reduce stigma and improve social integration for adolescents who engage in deviant behavior. In the long term, these results can be implemented in social practice to develop more effective and contextually relevant models of culture-based interventions. This research makes an important contribution to the social intervention approach by offering insights into the potential of local ethics in supporting the formation of adolescent characters in a community-based environment.